2022
DOI: 10.51791/njap.v49i3.3551
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and gut health of broilers fed Moringa oleifera and Azardiracta indica as an alternative to antibiotics

Abstract: High usage of antibiotics has led to an increase in bacteria developing antibiotic resistance. A resistant strain of human pathogenic bacteria has been found in the non-curative usage of antibiotics for animal production. Moringa oleifera and Azardiracta indica are phytobiotics which have been proven to be natural, with no residual effect and are thought to be ideal for animal production. An experiment was conducted to determine the growth performance and gut health of broilers fed Moringa oleifera and neem Az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This could benefit the poultry industry by improving food safety, health, and economics ( 66 ). There are varying opinions on the benefits of M. oleifera supplementation in poultry ( 67 ), whereas MOLP feed has been reported to improve intestinal permeability and digestive function and favorably modulate the composition of the gut microbiota ( 68 ). This could potentially benefit the overall health of the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could benefit the poultry industry by improving food safety, health, and economics ( 66 ). There are varying opinions on the benefits of M. oleifera supplementation in poultry ( 67 ), whereas MOLP feed has been reported to improve intestinal permeability and digestive function and favorably modulate the composition of the gut microbiota ( 68 ). This could potentially benefit the overall health of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that adding M. oleifera to chicken feed can improve growth, immunity, anticoccidial activity, blood biochemistry (62), antibacterial activity, and antioxidant activity (63)(64)(65). This could benefit the poultry industry by improving food safety, health, and economics (66). There are varying opinions on the benefits of M. oleifera supplementation in poultry (67), whereas MOLP feed has been reported to improve intestinal permeability and digestive function and favorably modulate the composition of the gut microbiota (68).…”
Section: Discussionmentioning
confidence: 99%